Nascent Ribo-Seq measures ribosomal loading time and reveals kinetic impact on ribosome density - Schott, Johanna; Reitter, Sonja; Lindner, Doris; Grosser, Jan; Bruer, Marius; Shenoy, Anjana; Geiger, Tamar; Mathes, Arthur; Dobreva, Gergana; Stoecklin, Georg (Nature methods, 2021)
In general, mRNAs are assumed to be loaded with ribosomes instantly upon entry into the cytoplasm. To measure ribosome density (RD) on nascent mRNA, we developed nascent Ribo-Seq by combining Ribo-Seq with progressive 4-thiouridine labeling. In mouse macrophages, we determined experimentally the lag between the appearance of nascent mRNA and its association with ribosomes, which was calculated to be 20-22 min for bulk mRNA. In mouse embryonic stem cells, nRibo-Seq revealed an even stronger lag of 35-38 min in ribosome loading. After stimulation of macrophages with lipopolysaccharide, the lag between cytoplasmic and translated mRNA leads to uncoupling between input and ribosome-protected fragments, which gives rise to distorted RD measurements under conditions where mRNA amounts are far from steady-state expression. As a result, we demonstrate that transcriptional changes affect RD in a passive way.